Diabetes Management and Outcomes among Patients with Type 2 Diabetes Attending a Renal Service - Elizabeth Skalkos; Rohit Rajagopal; David Simmons (Journal of Diabetes Research)
Background. Patients with comorbid type 2 diabetes mellitus (T2DM) and renal disease, particularly those treated with insulin, often require complex pharmacological treatment and management of other diabetes complications. Aims. To assess the achievement of metabolic targets and compare the current management of renal service attenders with insulin- and noninsulin-treated T2DM. Methods. Single-centre retrospective cross-sectional study involving medical record review of patients with T2DM aged ≥18 years who visited a metropolitan renal outpatient clinic in 2017. Univariable analysis and multivariable logistic regression were used to identify factors associated with insulin treatment. Results. Among 268 patients (45.5% insulin-treated), mean HbA1c was higher in insulin-treated vs. noninsulin-treated patients (8.0±1.8% (64 mmol/mol) vs. 6.8±1.2% (51 mmol/mol), p<0.001). Significantly fewer insulin-treated patients had HbA1c≤7.0% (53 mmol/mol; 31.8% vs. 69.3%, p<0.001). More insulin-treated patients had ischaemic heart disease (46.7% vs. 33.6%, p=0.028), diabetic foot disease (15.6% vs. 4.8%, p=0.003), retinopathy (40.2% vs. 11.0%, p<0.001), and emergency attendance for severe hypoglycaemia (3.8% vs. 0% p=0.042). Insulin treatment was more associated with chronic kidney disease stages 4-5 (adjusted odds ratio (aOR) 2.41, 95% CI 1.07-5.43), retinopathy (aOR 3.10, 95% CI 1.04-9.27), and podiatry review (aOR 5.06, 95% CI 1.20-21.38). Only 38 (14.2%) individuals were seen by a colocated public multidisciplinary diabetes service in 2017. Conclusions. Renal clinic attenders with T2DM, particularly if insulin-treated, remained at increased risk of diabetes-related complications, including severe hypoglycaemia, with limited input from the colocated hospital diabetes team. Approaches to increase coordination of diabetes care among renal patients should be investigated.